Little evidence for fire-adapted plant traits in Mediterranean climate regions - Bradshaw, S.; Dixon, Kingsley; Hopper, S.; Lambers, H.; Turner, S. (2011)
As climate change increases vegetation combustibility, humans are impacted by wildfires through loss of lives and property, leading to an increased emphasis on prescribed burning practices to reduce hazards. A key and pervading concept accepted by most environmental managers is that combustible ecosystems have traditionally burnt because plants are fire adapted. In this opinion article, we explore the concept of plant traits adapted to fire in Mediterranean climates. In the light of major threats to biodiversity conservation, we recommend caution in deliberately increasing fire frequencies if ecosystem degradation and plant extinctions are to be averted as a result of the practice.